Diagnostic Accuracy of Magnetic Resonance Imaging Knee in Diagnosis of Anterior Cruciate Ligament Tear Taking Arthroscopy as Gold Standard - Khan, Remsha Hameed; Iqbal, Javed; Ahmad, Adnan; Kamal, Seemab (Indus Journal of Bioscience Research, 2025)
Background: Anterior cruciate ligament (ACL) tears are knee injuries that commonly occur and may severely affect the quality of joint function. Diagnosis of an ACL tear is commonly done with MRI, but accuracy will be dependent on several factors. Objective: To determine the diagnostic accuracy of magnetic resonance imaging knee in diagnosis of anterior cruciate ligament tear taking arthroscopy as gold standard. Study Design: Cross-sectional validation study. Duration and Place of Study: The study was conducted from January 2024 to June 2024 at the Radiology Department of Lady Reading Hospital, Peshawar. Methodology: A total of 160 patients between 18–60 years of age with symptoms consistent with ACL tears were enrolled. The imaging sequences used for MRI included a variety of different sequences on a Toshiba 1.5T machine. All patients underwent arthroscopic evaluation and results were compared with MRI findings. Results: The mean age of participants was 30.0 ± 9.29 years. MRI identified 132 positive cases (82.5%) and 28 negative cases (17.5%), while arthroscopy confirmed 136 positive cases (85%) and 24 negative cases (15%). The diagnostic accuracy of MRI was 86%, with a sensitivity of 90%, specificity of 63%, positive predictive value (PPV) of 93%, and negative predictive value (NPV) of 54%. Conclusion: MRI is a safe and noninvasive modality for ACL tear detection with a diagnostic accuracy similar to arthroscopy.